„Time is a Disease for the Cosmos, and a Tree of Life for Us”. The Metaphysics of Time in the Prose of Mikhail Shishkin .......... 557 - Tyszkowska-Kasprzak, Elżbieta (Czas w kulturze rosyjskiej, 2019)
„TIME IS A DISEASE FOR THE COSMOS, AND A TREE OF LIFE FOR US”. THE METAPHYSICS OF TIME IN THE PROSE OF MIKHAIL SHISHKINThe novels of Mikhail Shishkin: The Taking of Izmail (2000), Maidenhair (2005), The Light and the Dark (2010), often reflect the theories and beliefs of old philosophers about time. One can observe a special polyphony in the ideas about time – its essence, origin, and relation to eternity – which are presented in Shishkin’s works. The writer outlines different views connected with time, although he predominantly relies on the concepts of Plato, by distinguishing between time and eternity, and by recognizing the fleetingness of the material world and the permanence of the existence of the universe. The opposition of eternity and time, just like in the philosophy of the Greek thinker, has a binary character: the original – a copy, the real being – a likeness. The eternity of the soul and the provisional nature of the earthly life are particularly important in Shishkin’s worldview. The author also refers to the ideas of Saint Augustine, who developed Plato’s thought and incorporated it into Christian religious philosophy. The transience of the body, so often shown in the writer’s works, contrasts with eternity and the immortality of the soul. Time given to man on earth should serve his improvement, therefore the time of our worldly life should be deepened, not prolonged. Shishkin admits that the role of the writer is to leave the reader with the hope of achieving eternity.